Determinan Kepatuhan Kunjungan Antenatal Care Pada Ibu Hamil - Mukhammad Himawan Saputra; Dwi Helynarti Syurandhari; Firlana Fajr Arsyad Tjiptania; Arief Fardiansyah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain major public health challenges in Indonesia. Improving compliance with antenatal care (ANC) visits is essential to reduce pregnancy-related complications and prevent maternal and neonatal mortality. This study aimed to examine the association between maternal age, educational level, and parity with compliance to ANC visits at Puskesmas Sidotopo Wetan, Surabaya City. This study employed an analytical correlational design with a cross-sectional approach. A total of 312 pregnant women who utilized ANC services in 2024 were included using total sampling. Data were obtained from secondary records and analyzed using the Spearman Rho correlation test with a significance level of ? = 0.05. The results showed that educational level was significantly associated with ANC compliance (p = 0.038), indicating that higher education was related to better adherence to recommended ANC visits. Parity also showed a significant relationship with ANC compliance (p = 0.023), suggesting that pregnancy experience influences maternal compliance behavior. In contrast, maternal age was not significantly associated with ANC compliance (p = 0.097). Most respondents were aged 20–35 years (80.4%), had a senior high school education (55.1%), were multiparous (69.2%), and overall ANC compliance remained low (38.1%). In conclusion, educational level and parity are important determinants of ANC compliance, while maternal age does not significantly influence adherence. Targeted health education and counseling interventions, particularly for pregnant women with lower educational levels and specific parity characteristics, are needed to improve ANC compliance and support maternal and neonatal health outcomes